Η βιβλιοθήκη του ελληνικού φιλολογικού συλλόγου Κωνσταντινουπόλεως (1863-1922) - Γιαννακόπουλος, Γιώργος Α. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1986)
The intellectual bloom of the Greek population of Asia Minor, which was observed from the middle of the 19th century onward, was expressed by the establishment of a great number of cultural associations. The most important of these was the «Greek Literary Association of Constantinople » (Syllogos), which played a primary role in the effort to strengthen the Greek language in Asia Minor. The present study examines the creation and operation of the public library of the Association, which was founded in 1863 and constituted one of the main activities of the Syllogos and one of the major instruments for the promotion of its cultural projects. The library’s history and mode of operation reflected the strengths and the weaknesses of Syllogos. The library was destroyed by fire in 1870 but soon it was recreated. Its further development was based mainly on a great number of donations of books by members of the Association and other individuals. Another major source for the enrichment of the library were exchanges with some of the most significant scientific institutions of Europe and America of the time. Over the years the library’s holdings grew to 27.000 volumes of printed books. The collection included 183 Greek manuscripts as well. Many of the second copies of books available in the library were sent to the libraries of Greek schools and the local associations in Asia Minor. The defeat of the Greek army in Asia Minor brought the end of Syllogos. The contents of the library were transferred to Ankara and dispersed to a number of Turkish scholarly institutions. The most important part went to the «Turkish Historical Association» (Turk Tarili Kurumy).